Verificação da satisfação da comunidade acadêmica UTFPR-Ct em relação ao ambiente universitário e à inserção urbana: subsídio para o Plano Diretor Participativo (PDP) do campus - Del Roio, Iolanda Geronimo (2024)
It is relevant to analyze the environment to size its qualitative aspects, in order to meet inter-relational demands, taking into account the different perspectives of users’ perceptions. Regarding the university environment, the Participatory Master Plan (PDP) is used as a regulatory strategy for areas on university campuses. The general objective of the research was to verify the satisfaction of the academic community (faculty, students, technical-administrative staff and outsourced workers) based on cognitive perception in relation to the campus environment of the Federal Technological University of Paraná campus Curitiba (UTFPR-CT), as well as as well as the urban insertion of the Headquarters (Centro, Ecoville and Neoville), aiming to contribute to the elaboration of the university’s Participatory Master Plan. This research collected data regarding the cognitive perception of satisfaction of the UTFPR-CT academic community from an environmental, social and work point of view (teaching, research and extension). Based on the Survey procedure method, the survey of subjective cognitive perception corroborates the provision of tangible actions related to the PDP of the Curitiba campus. Through the Survey, in the months of October and November 2023, qualitative satisfaction data was collected via a questionnaire using the Google Form, which, as it is statistically treatable, revealed the quantitative nature of the cognitive perception of the institution’s academic community. The data were processed using SPSS (Statistical Package for the Social Science) software. A sample was collected with 766 respondents, made up of students, teachers, administrative technicians and outsourced workers from UTFPR-CT, made up of the Centro, Ecoville and Neoville Headquarters. Survey was based on descriptive and multivariate statistical analyzes (factorial, correlation and discriminant). The variables measured by satisfaction represent the groups of Satisfaction with Headquarters (SS) and Satisfaction with the Surroundings (SE). The groups Bioclimatic (BC), Comfort of Built Space (CE) and Accessibility (AC) measure perceived quality. The descriptive analysis took into account eight variables from three constructs to compose the Headquarters sample profile. The Factor – Location (L), coming from SS and SE, presented a greater range of perception of the variables between the Central Headquarters and the Ecoville and Neoville Headquarters. Still comparing these Headquarters, another aspect that clearly differs is in relation to the Factor – Green Areas (AV), originating from CE. As the Neoville Headquarters includes a forest on its campus, the Quality of Green Areas (AV1) has a high quality and satisfactory perception from the users’ perspective. The values of the perception of General Satisfaction with Headquarters (SS6) in relation to the Headquarters are not discrepant and present a certain indifference. Finally, the research supports the conditions for building a policy for the use and occupation of spaces, through the UTFPR-CT PDP, based on the diagnosis of the reality of the academic community presented with a view to the relational qualities revealed.